2012
DOI: 10.1093/pcp/pcs076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Target Site of Aluminum Phytotoxicity in Photosynthetic Electron Transport by Fluorescence Techniques in Tobacco Leaves

Abstract: Aluminum (Al) toxicity limits crop yield in acidic soil through affecting diverse metabolic processes, especially photosynthesis. The aim of this work was to examine the effect of Al on photosynthetic electron transport in vivo as determined by chlorophyll fluorescence and delayed fluorescence of tobacco leaves. Results showed that Al treatment inhibited the photosynthetic rate and electron transfer, and decreased photosystem (PS) II photochemical activity in a time- and concentration-dependent manner, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 47 publications
3
46
0
Order By: Relevance
“…Under its trivalent cationic form, Al 3+ acts as a highly toxic non-essential element for plants growth causing a number of adverse effects on physiological and biochemical processes, especially the inhibition of photosynthetic activity. At this level, it was shown that Al 3+ inhibits photosynthetic electron transport in photosystem II (PSII), affects the PSII RC, destabilizes the oxygen evolution complex (OEC), impairs light harvesting complex (LHCII) antenna of PSII and induces a conformational changes of the secondary structure polypeptides of PSII [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Under its trivalent cationic form, Al 3+ acts as a highly toxic non-essential element for plants growth causing a number of adverse effects on physiological and biochemical processes, especially the inhibition of photosynthetic activity. At this level, it was shown that Al 3+ inhibits photosynthetic electron transport in photosystem II (PSII), affects the PSII RC, destabilizes the oxygen evolution complex (OEC), impairs light harvesting complex (LHCII) antenna of PSII and induces a conformational changes of the secondary structure polypeptides of PSII [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Our early studies showed that protoplasts exhibited an increase of ROS levels in a light-dependent manner after UV-C irradiation [9]. Recently, some studies demonstrated that various stimuli, such as aluminum toxicity, methyl jasmonate treatment and pathogen attack, can cause chloroplast dysfunction and photosynthetic damage as well as chloroplastic ROS production [10][11][12]. Studies showing the function of ROS in signal transduction networks during plant PCD process have started to emerge [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The cryo-fractured specimens were dried using freeze-drier, coated with carbon and prepared for observation by SEM. A portable version of an Imaging-PAM Chlorophyll Fluorometer (PAM-MINI, Walz, Effeltrich, Germany) connected to a computer with data acquisition software (ImagingWin v2.0 m, Walz) was used to determine the chlorophyll fluorescence parameters (Li et al, 2012a). Leaves were adapted in darkness for at least 15 min for precise determination of minimal and maximal fluorescence levels in the dark (F o and F m , respectively).…”
Section: Leaf Morphological and Chlorophyll Fluorescence Parametersmentioning
confidence: 99%